Separating families, recuperating the "nation-as-family": Migrant youth and the cultural politics of shame - Ethan Chang; Jill Koyama; Julie Kasper (Arizona State University, 2020)
This study investigates the intersections of policy, affect, and the lives of migrant youth. We approach the Trump Administration's contingent reversal of a "zero tolerance" family separation policy as an illustrative case for understanding how affect mediates policy-making processes. Combining Critical Policy Analysis (CPA) and affect studies, we analyze 184 print media texts between the declaration of zero tolerance (May 2018) and President Trump's repeal of his executive order (June 2018). We argue that mainstream media invited publics to sympathize with migrant youth and shame zero tolerance policy and its defenders. While shame catalyzed nationwide #KeepFamiliesTogether protests, it also animated political actions that recuperated "America" as a tolerant nation (e.g., "Love, not hate, makes America great"). In doing so, shame suppressed structural critiques of U.S. state violence toward migrant as well as Black, Indigenous, and minoritized families and youth. We conclude by discussing how a "pedagogy of discomfort" offers one way to build toward more historically responsive and intersectional coalitions for migrant and education justice.